Modelisation and simulation of pilotings systems for a training organization (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The current production systems are growing in complexity. This complexity results for a large share of market demand, competition, quality and the density and diversity of products they handle. A typical example of a complex system, commonly used in the industry is that structures flexible job-shop. These systems are able to adapt to possible changes of the environment. They have a large variety of product flows with arbitrary sequences of production, including cyclical phases (multiple operations of the same flows on the same resource). The objective associated with this type of system is then to ensure treatment varied as possible with maximum productivity at lower cost.